PASAR LELANG KOMODITI AGRO (PLKA) SEBAGAI ALTERNATIF PEMASARAN PRODUK PERTANIAN DI PROVINSI SULAWESI UTARA - Martin S. Mirah; Caroline B.D. Pakasi; Esry H. Laoh; Ellen G. Tangkere (Universitas Sam Ratulangi, 2017)
ABSTRACTThis trading system is built to generate high agro commodity competitiveness through increased market access. To support the trading system then this system must have some advantages. This writing aims to describe the number of commodities and products transacted in the Auction Market of Agro Commodities as an alternative to the marketing of agricultural products. This research will be conducted for 3 months from May to July starting from preparation of data up to the preparation of research result report. The research is located in North Sulawesi Province. The data used is secondary obtained from the Department of Industry and Trade Pronvinsi Sulawesi Utara with existing data. The data obtained in this study will be analyzed by using descriptive analysis and will be presented in tabular form. The results of this study can be seen from describing the transactions that occur Hybrid Corn Commodity is consistently available and create a contract agreement, while Kopra commodity although not consistent but the contract agreement is greater than other commodities.Keywords : Market, Commodities, Agro